Driving forces of the spatiotemporal supply pattern of runoff in the source region of Yellow River - Zongjie Li; Fang Liu; Hao Li; Mengqing Liu; Zongxing Li; Qi Feng; Bin Xu; Xiaoying Liu (Journal of Hydrology: Regional Studies)
Study region: Source Region of Yellow River, China Study focus: Studies on the impacts of permafrost degradation on the hydrological cycle in cold regions using stable isotope tracing are relatively scarce. In this study, we investigated the spatiotemporal supply patterns and mechanisms of runoff in source region of Yellow River, China, from June to September, using end-member mixing analysis. New hydrological insights for the region: The results indicated that the monthly changes observed in stable isotopes across different waterbodies, along with their relation to the local meteoric water line, revealed that atmospheric precipitation contributed the most significantly to runoff in August. Contributions from precipitation, supra-permafrost water, and glacial snow meltwater to total runoff were 71, 24, and 5 %, respectively, at the river outlet. In June, these contributions were 53, 40, and 7 %, respectively; in July, 81, 14, and 5 %; in August, 86, 10, and 4 %; and in September, 63, 34, and 3 %. Precipitation and supra-permafrost water increased initially and then decreased, while glacial snow meltwater consistently declined. At higher altitudes, glacial snow meltwater played a more prominent role in runoff recharge, whereas supra-permafrost water was less influenced by altitude. Overall, precipitation was found to be the primary source of runoff, followed by supra-permafrost water and then glacial snow meltwater in source region of Yellow River, China.